2013
DOI: 10.3892/ol.2013.1270
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of Rh123high stem-like cells in a side population of 786-O renal carcinoma cells

Abstract: The aim of the present study was to investigate the differences in biological characteristics between the rhodamine 123 (Rh123)high and Rh123low subpopulations of the renal cancer cell line 786-O and to identify evidence for the existence of cancer stem cells in renal cell carcinoma (RCC) cells. In vitro cultured RCC 786-O cells were stained with Rh123, analyzed and sorted with flow cytometry. The differences in proliferative activity, long-term differentiation and radiation sensitivity between the two subpopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…Most of this evidence is based on tumor-tissue-specific SCLCCs, while some are based on RCC cell lines [1820, 42, 43]. SCLCCs have been identified from RCC cell lines based on chemokine receptor CXCR4 [19, 42] and side population cell selection by aldehyde dehydrogenase activity [18, 20, 43], Hoechst 33342 dye [44] and rhodamine 123 [45]. Previously, Bussolati et al observed renal carcinoma specimens from patients after radical nephrectomy, which showed CD105+ subpopulation is enrich for tumor-initiating cells (TICs) [31] and tumor angiogenesis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Most of this evidence is based on tumor-tissue-specific SCLCCs, while some are based on RCC cell lines [1820, 42, 43]. SCLCCs have been identified from RCC cell lines based on chemokine receptor CXCR4 [19, 42] and side population cell selection by aldehyde dehydrogenase activity [18, 20, 43], Hoechst 33342 dye [44] and rhodamine 123 [45]. Previously, Bussolati et al observed renal carcinoma specimens from patients after radical nephrectomy, which showed CD105+ subpopulation is enrich for tumor-initiating cells (TICs) [31] and tumor angiogenesis [46].…”
Section: Discussionmentioning
confidence: 99%
“…The ACHN line CSC subpopulation is Hoechst33342-negative and ALDH-positive [98], while Caki-2 CSCs are also ALDH-positive and form spheres [99]. The 786-O cell line is also shown to bear the CSC subpopulation, as confirmed by Rh123 fluorescent intensity based isolation [105]. At the same time, SK-RC-42 cells cultured in spheres have features of CSCs [90].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Rh123 staining, RCC cells were characterized as Rh123 high and Rh123 low cells in a recent study [39]. Serially transplanted Rh123 high cells into SCID mice were able to form tumours in all cases (12/12 cases).…”
Section: Introductionmentioning
confidence: 99%